Analisis Faktor Ketidaktepatan Kode Diagnosa Pasien Rawat Inap Terhadap Pending Klaim Bpjs Kesehatan di Rsud Sekarwangi - Vivi Widayanti; Yuyun Yunengsih (Jurnal Infokes, 2026)
Sekarwangi Regional Public Hospital (RSUD Sekarwangi) has established a Standard Operating Procedure (SOP) that governs the submission process for BPJS Health claims. Claims are only accepted by BPJS Health if they comply with the prescribed procedures and flow. If a claim file does not meet the applicable requirements, BPJS Health will return it to the hospital for revision before it can proceed to the reimbursement stage. The purpose of this study is to analyze the factors causing inaccuracies in inpatient diagnosis coding that lead to pending BPJS Health claims at RSUD Sekarwangi. This research employs a descriptive quantitative method. Data collection techniques include observation and literature review. The sample in this study consists of claim files with pending status from October to November 2024. Based on the findings, out of a total of 4,275 submitted claim files, 1,258 files (23%) were marked as pending during the fourth quarter of 2024 at RSUD Sekarwangi. These problematic files were categorized into three main factors: coding errors, the need for code reselection, and the presence of duplicate codes. Based on these findings, it is recommended that the hospital’s coding department improve accuracy and precision during the coding process and in preparing claim documents. In addition, staff members are advised to update their knowledge regarding diagnosis coding and review the BPJS Health guidelines to minimize misinterpretation between the hospital coders and the verifiers.